2006
DOI: 10.21897/rmvz.1043
|View full text |Cite
|
Sign up to set email alerts
|

Ecología trófica de la doncella (Ageneiosus pardalis Lütken, 1874) en la cuenca del Río Sinú, Colombia

Abstract: Objetivo. Se estudió la ecología trófica de la doncella (Ageneiosus pardalis Lütken, 1874) en la cuenca del río Sinú entre enero y diciembre 2002. Materiales y Métodos. El contenido estomacal se evaluó con el coeficiente de vacuidad, grado de llenado, grado de digestión, frecuencia de ocurrencia, frecuencia numérica, gravimetría, índice de importancia relativa (IIR) y la relación longitud intestinal (LI)-longitud total (LT). Resultados. El 58.3% de los estómagos se encontró vacío y el 6.4% de las presas en est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Linolenic acid (18:3 n-3) was not detected in P. magdaleniatum or P. magdalenae, which is in agreement with a previous report on P. magdaleniatum (Perea et al, 2008). Polyunsaturated fatty acids n-3 were not detected in A. pardalis, which may reflect preferences in the diet, mainly composed of other fish, occasionally crustacean, insects and other trophic groups (Tobías-Arias et al, 2006).…”
Section: Fatty Acids Identified In the Three Species In The Two Seasonsmentioning
confidence: 86%
See 2 more Smart Citations
“…Linolenic acid (18:3 n-3) was not detected in P. magdaleniatum or P. magdalenae, which is in agreement with a previous report on P. magdaleniatum (Perea et al, 2008). Polyunsaturated fatty acids n-3 were not detected in A. pardalis, which may reflect preferences in the diet, mainly composed of other fish, occasionally crustacean, insects and other trophic groups (Tobías-Arias et al, 2006).…”
Section: Fatty Acids Identified In the Three Species In The Two Seasonsmentioning
confidence: 86%
“…The freshwater fishes Prochilodus magdalenae (bocachico), Pseudoplatystoma magdaleniatum (catfish) and Ageneiosus pardalis (doncella) are the most highly-demanded Colombian species because of the quality of their meat, size, and taste. These species differ in their feeding preferences, while P. magdalenae is detritivorous (Bowen, 1983, Flecker, 1996, P. magdaleniatum (Jiménez-Segura, 2009) and A.pardalis (Tobías-Arias et al, 2006) are carnivorous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atencio-García et al (2005) recorded fishes and macrocrustaceans in the diet of A. pardalis. Tobías-Arias et al (2006) observed that A. pardalis feeds mainly on fishes, crustaceans and insects, in addition to other items identified by the authors as plant remains and unidentified material.…”
Section: Ecological Notesmentioning
confidence: 67%
“…Tobías‐Arias et al . () observed that A . pardalis feeds mainly on fishes, crustaceans and insects, in addition to other items identified by the authors as plant remains and unidentified material.…”
Section: Key To the Identification Of Species Of Ageneiosusmentioning
confidence: 95%